979. ACER STACHYOPHYLLUM: Sapindaceae. (30th May 2021) - Crowley, Dan; Rix, Martyn
Summary: Acer stachyophyllum Hiern. is illustrated. Recent collections are described, and its value as a garden tree is assessed.